Effect of perineal massage and gentle techniques on perineal rupture in primigravida maternity mothers - Annisa Tania Dewi; Dedah Jubaedah; Feby Pebryanti Suhendi; Intan Friasta; Yeli Yuliani; Ageng Septa Rini; Shinta Mona Lisca (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Background: Perineal rupture is a tear that occurs when a baby is born, either spontaneously or by using tools/actions. Preventive efforts can be made to reduce the risk of perineal rupture by massaging the perineum and using good pressure techniques during labor. Objective: To determine the effect of perineal massage techniques and pressure on perineal rupture in primigravida mothers who give birth. Method: This research uses experimental research methods; this type of research is quantitative with a pretest-posttest research design with a control group and an analytical study design with a retrospective approach. The total research sample required was 30 primigravidas, with details, namely 15 people from the perineal massage group and 15 from the gentle technique. Sampling was taken using an accidental sampling technique, where subjects were selected as research samples based on cases/respondents who happened to be available in a place according to the context. Results: research results of primigravid mothers who experienced perineal rupture in the perineal massage group were two people (20%), and in the menstrual technique group, there were eight people (80%), based on the results of data analysis using the Wilcoxon test, the p-value was obtained. In the perineal massage group, it was 0.000; in the gentle technique group, it was 0.005. Conclusion: It can be concluded that perineal massage is more effective than gentle techniques in preventing perineal rupture in primigravida mothers. To ensure the effectiveness of the chosen method, it is advisable to consult with medical personnel experienced in this field and follow the recommendations and protocols approved by the relevant health authorities. In addition, careful monitoring and care during labor is also essential to minimize the risk of perineal rupture.